Behavioral Leadership Accountability and Public Service Outcomes in Municipal Government: Evidence from Gorontalo - Umar Sako; Zshyna Mae V. Ahmed; Muh. Akmar M; Dharmawaty S. Makur; Joice Machmud (Publisia: Jurnal Ilmu Administrasi Publik, 2026)
This study addresses the persistent gap between formal accountability mechanisms and actual public service outcomes, particularly in decentralized governance contexts where procedural compliance often fails to translate into performance improvement. While existing studies predominantly conceptualize accountability as a structural mechanism, limited attention has been given to its behavioral dimensions in shaping administrative outcomes. This study aims to examine the effect of behavioral leadership accountability on public service outcomes and to analyze the mediating roles of employee engagement and public trust. A quantitative explanatory approach was employed using a purposive sampling technique targeting 162 municipal leaders and mid-level managers with direct involvement in public service delivery. Data were collected through structured questionnaires and supported by secondary performance indicators. Structural Equation Modeling–Partial Least Squares (SEM-PLS) was used to analyze both direct and indirect relationships. The results show that behavioral leadership accountability has a significant positive effect on public service outcomes (β = 0.61, p < 0.001), explaining 58% of performance variance. Employee engagement and public trust partially mediate this relationship. This study contributes theoretically by reconceptualizing accountability as a behavioral construct and empirically by providing evidence from a decentralized governance context, while also offering practical insights for leadership-driven accountability reforms.